Drought tolerance in grapevine involves multiple interacting physiological mechanisms - Gambetta, Gregory; Delmas, Chloé; Marguerit, Elisa; Ollat, Nathalie; Saint Cast, Clément; van Leeuwen, Cornelis; Delzon, Sylvain (IVES technical reviews : vine & wine, 2024)
The past decade has produced some major advances in our understanding of how grapevines regulate their water use and tolerate drought. Numerous traits that are important for conferring drought tolerance have been identified and quantified across a range of cultivars (Dayer et al., 2022). Nevertheless, arriving at a firm hierarchical rating of different cultivars’ drought tolerance has eluded scientists. This short review seeks to explain how drought tolerance is dependent on multiple traits, all interacting within a particular environment and management context.